PENGARUH TRANSPARANSI DAN KOMITMEN TERHADAP AKUNTABILITAS PENGELOLAAN ANGGARAN - Henny Hendratmi; JMV Mulyadi; Tri Widiastuti (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2017)
This study aims to examine and analyze the effect of transparency and commitment to the budget management in Bekasi City simultaneously and partial in period 2014. This study uses the population, namely the budget administrator and representatives of school committees Bekasi City where in 2014 the number of high school by 70. Meanwhile, samples took as many as 210 respondents by cluster sampling method and used primary data by distributing questionnaires. From this study we concluded that transparency and commitment have simultaneously positive and significant implications againts the accountability of budget management. Furthermore the research has proved that the applied commitment positively effect to the achievement of management accountability.Keywords: Budget Management Accountability, Transparency, Commitment